ANALYSIS OF EXPENDITURE BUDGET PERFORMANCE AT THE WONOSOBO REGENCY GENERAL ELECTION COMMISSION (KPU) FROM 2020 TO 2024 - Lailatul Azizah; Romandhon Romandhon; Susanti Susanti (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the performance of the Wonosobo Regency General Election Commission's budget in 2012-2016. The analysis used includes: analysis of expenditure variance, analysis of expenditure growth, analysis of expenditure harmony and expenditure efficiency ratio. This analysis is appropriate to use because it can measure the use of the expenditure budget economically, effectively and efficiently. The method used is a qualitative method processed using descriptive analysis. The data used is a budget realization report obtained directly from the Wonosobo Regency General Election Commission. Based on the results of the study, it can be seen that: (1) the results of the expenditure variance analysis and analysis of expenditure growth at the General Election Commission have been running well; (2) the analysis of expenditure harmony shows that the KPU is still lacking in harmonizing expenditures, especially capital expenditures; (3) the Wonosobo Regency General Election Commission has carried out efficiency by using the budget not exceeding its realization. Overall, the performance of the Wonosobo Regency KPU's expenditure budget in 2020-2024 is good.